Subthalamic nucleus stimulation in tremor dominant parkinsonian patients with previous thalamic surgery. Issue 2 (14th January 2005) - Fraix, V; Pollak, P; Moro, E; Chabardes, S; Xie, J; Ardouin, C; Benabid, A L
Abstract : Before the introduction of high frequency stimulation of the subthalamic nucleus (STN), many disabled tremor dominant parkinsonian patients underwent lesioning or chronic electrical stimulation of the thalamus. We studied the effects of STN stimulation in patients with previous ventral intermediate nucleus (VIM) surgery whose motor state worsened. Fifteen parkinsonian patients were included in this study: nine with unilateral and two with bilateral VIM stimulation, three with unilateral thalamotomy, and one with both unilateral thalamotomy and contralateral VIM stimulation. The clinical evaluation consisted of a formal motor assessment using the Unified Parkinson's Disease Rating Scale (UPDRS) and neuropsychological tests encompassing a 50 point frontal scale, the Mattis Dementia Rating Scale, and the Beck Depression Inventory. The first surgical procedure was performed a mean (SD) of 8 (5) years after the onset of disease. STN implantation was carried out 10 (4) years later, and duration of follow up after beginning STN stimulation was 24 (20) months. The UPDRS motor score, tremor score, difficulties in performance of activities of daily living, and levodopa equivalent daily dose significantly decreased after STN stimulation. Neither axial symptoms nor neuropsychological status significantly worsened after the implantation of the STN electrodes. The parkinsonian motor state is greatly improved by bilateral STN stimulation even in patients with previous thalamic surgery, and STN stimulation is more effective than VIM stimulation in tremor dominant parkinsonian patients.